A Novel Ternary CoFe2O4/CuO/CoFe2O4 as a Giant Magnetoresistance Sensor - Ramli Ramli; Ambran Hartono; Edi Sanjaya; Ahmad Aminudin; Khairurrijal Khairurrijal; Freddy Haryanto; Cuk Imawan; Mitra Djamal (Institute for Research and Community Services (LPPM) ITB, 2016)
This paper reports the results of a study relating to the synthesis of a novel ternary CoFe2O4/CuO/CoFe2O4 thin film as a giant magnetoresistance (GMR) sensor. The CoFe2O4/CuO/CoFe2O4 thin film was prepared onto silicon substrate via DC magnetron sputtering with the targets facing each other. X-ray diffraction was used to determine the structure of the thin film and a 4-point method was used to measure the MR ratio. The GMR ratio is highly dependent on the ferrimagnetic (CoFe2O4) and nonmagnetic (CuO) layer thickness. The maximum GMR ratio at room temperature obtained in the CoFe2O4/CuO/CoFe2O4 thin film was 70% when the CoFe2O4 and the CuO layer had a thickness of 62.5 nm and 14.4 nm respectively.